2014
DOI: 10.1177/0095798414550864
|View full text |Cite
|
Sign up to set email alerts
|

Beauty and Body Image Concerns Among African American College Women

Abstract: The current study examined body image concerns among African American women. In recent years, there has been an attempt to include ethnic minority samples in body image studies (e.g., Grabe & Hyde, 2006; Hrabosky & Grilo, 2007; Lovejoy, 2001) but few specifically examine unique issues pertaining to beauty and body image for African American college age women. A total of 31 African American women participated in one of five focus groups on the campus of a large Southwestern University to examine beauty and body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
118
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(123 citation statements)
references
References 42 publications
4
118
0
1
Order By: Relevance
“…In contrast, more positive marital attitudes had a weaker dampening effect on risky sexual behavior for darker skin individuals than lighter skin individuals as darker skin individuals may view marriage as a less attainable option. Such findings are consistent with evidence suggesting that darker skin individuals, particularly women, may be losing hope that committed relationships and marriage are attainable (Awad et al 2014; Boylorn 2012; Ferdinand 2015; Wilder and Cain 2011), therefore marriage and cohabitation attitudes do little to offset their engagement in risky sexual behavior. All these significant links emerged among specific racial/ethnic minority groups: African Americans and Asians.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In contrast, more positive marital attitudes had a weaker dampening effect on risky sexual behavior for darker skin individuals than lighter skin individuals as darker skin individuals may view marriage as a less attainable option. Such findings are consistent with evidence suggesting that darker skin individuals, particularly women, may be losing hope that committed relationships and marriage are attainable (Awad et al 2014; Boylorn 2012; Ferdinand 2015; Wilder and Cain 2011), therefore marriage and cohabitation attitudes do little to offset their engagement in risky sexual behavior. All these significant links emerged among specific racial/ethnic minority groups: African Americans and Asians.…”
Section: Discussionsupporting
confidence: 85%
“…For example, a participant in a recent qualitative study illustrated this point stating “None of the boys wanted to marry me because I was too dark and they were already asking me “you know your children are going to come out really, really dark and that's not good.” But my light skinned friend got married to a different boy every day. But, I didn't because I wasn't light enough, and that really hurt my feelings, and to this day, it still brings me back to the idea that I'm not good enough” (Awad et al 2014, p. 550). Assuming darker skin individuals are aware of social preferences for lighter skin, darker skin individuals as compared to lighter skin individuals, may anticipate fewer prospects for mate selection and marriage and, in turn, view marriage as a less attainable option.…”
Section: Introductionmentioning
confidence: 99%
“…When colorism is considered alongside gender and race inequalities, it becomes apparent that darker‐skinned African American women may have more limited mate choices than one might expect from an examination of race or gender alone (Hamilton et al, ). As one young woman interviewed by Awad et al () said:
None of the boys wanted to marry me because I was too dark and they were already asking me “you know your children are going to come out really, really dark and that's not good.” But my light skinned friend got married to a different boy every day. But, I didn't because I wasn't light enough, and that really hurt my feelings, and to this day, it still brings me back to the idea that I'm not good enough.
…”
Section: Terms Of Social Exchange From a Colorism Perspective: A Focumentioning
confidence: 99%
“…Similar to how Black women stereotypes may influence Black women's self‐concept, the glorification of Eurocentric standards of beauty (e.g., fair skin, straight hair) challenge a Black woman's understanding of her physical self. In a qualitative study focusing on Black women's ideas of beauty and body image, Awad and colleagues () found that Black women are cognizant of how aspects of their physical self, such as hair and skin tone, may dictate their self‐confidence, perceived attractiveness, and access to societal resources. Black women's considerations of these aspects of beauty even shape their perceptions of intimacy and dating relationships.…”
Section: Ethnocultural Concerns Of Black Women In Collegementioning
confidence: 99%
“…Stephens and Thomas () found that among Black college women, lighter skin was considered more attractive and perceived as more sexually appealing. Collectively, scholars agree that Black women may experience significant distress and conflict as they attempt to reject the internalization of Eurocentric standards of beauty while embracing themselves and other Black women as beautiful (Awad et al, ; Thomas, Hacker, & Hoxha, ).…”
Section: Ethnocultural Concerns Of Black Women In Collegementioning
confidence: 99%